Assessment of the preparedness of obstetrics and gynecology healthcare systems during the COVID‐19 pandemic in Libya. Issue 3 (7th July 2020) - Elhadi, Muhammed; Msherghi, Ahmed; Elgzairi, Moutaz; Alsuyihili, Ali; Elkhafeefi, Fatimah; Bouhuwaish, Ahmad; Biala, Marwa
Abstract : An adequate strategy is urgently required during the COVID‐19 pandemic for screening pregnant women and newborns, increasing infection control measures, and supplying personal protective equipment and hospital equipment.